Crossing borders, making connections interdisciplinarity in linguistics - Ardoin, Sonja; Barrett, Rusty; Brett Dunstan, Stephany; Burkette, Allison; Cavanaugh, Jillian R.; Childs, Becky; Grieser, Jessica A.; Hamilton, Heidi E.; Hirshman, Amy J.; Jason Coker, K.; Kroskrity, Paul V.; Lauersdorf, Mark Richard; et al. (Interdisciplinary Linguistics ;, 2021)
This edited volume explores the scope of interdisciplinary linguistics and includes voices from scholars in different disciplines within the social sciences and humanities, as well as different sub-disciplines within linguistics. Chapters within this volume offer a range of perspectives on interdisciplinary studies, represent a connection between different disciplines, or demonstrate an application of interdisciplinarity within linguistics. The volume is divided into three sections: perspectives, connections, and applications. Perspectives The goal of this section is to address more generally the definition(s) of and value of multi-, trans-, and inter-disciplinary work. In what areas and for what purposes is there a need for work that crosses discipline boundaries? What are the challenges of undertaking such work? What opportunities are available? Connections This section features paired chapters written by scholars in different disciplines that discuss the same concept/idea/issue. For example, a discussion of how "assemblage" works in archaeology is paired with a discussion of how "assemblage" can be used to talk about 'style' in linguistics. Applications This section can be framed as sample answers to the question: What does interdisciplinarity look like?